Health Counseling and Cervical Cancer Screening Test for Reproductive Age Women in Bojong Gede District : Penyuluhan Kesehatan Deteksi Dini Kanker Serviks pada Wanita Usia Subur di Kecamatan Bojong Gede - Shinta Novelia; Bunga Tiara Carolin (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
In Indonesia, 75% of women have experienced vaginal discharge at least once in their lives and half of them have experienced vaginal discharge twice or more. Vaginal discharge is a classic problem for most women. Ironically, most women do not know about vaginal discharge and the causes of vaginal discharge. If not handled properly, vaginal discharge can be fatal, infertility and ectopic pregnancy (pregnancy outside the womb) can be one of the consequences of vaginal discharge. The early symptoms of uterine cancer usually start with vaginal discharge. The betel leaf (Piper betle linn) used in this study belongs to the Peiperaceae family. The part used is the leaves. Betel leaf contains essential oils that contain compounds that have strong antibacterial properties, which are referred to as "kavikol" and "kavibetol". Anti-bacterial is also found in boiled betel in water. Betel leaf in traditional medicine is usually used for first aid in first-line treatment in daily medicine, especially as an antiseptic. This activity aims to increase the knowledge of adolescent girls about the dangers of vaginal discharge and provide an intervention in the form of betel leaf boiled water to reduce physiological vaginal discharge. The results of the activity showed benefits for adolescents as evidenced by the decrease in the incidence of physiological vaginal discharge after being given counseling and betel leaf water.